Behind the fair facade a phenomenological study on TikTok Beauty Filters? influence towards female adolescents? self-image and self-esteem - Villar, Claire C.
TikTok, one of the most popular social media platforms in today's time, is a social networking app famous for allowing users to create short-form videos for entertainment. However, the rise of TikTok as a new media has led to the proliferation of beauty filters that alter one?s face and natural beauty to conform to Eurocentric beauty standards. As a result, beauty filters are one of the key sources of beauty insecurities for Filipino girls. Hence, this phenomenological study explored the lived experiences of female adolescents regarding their exposure to TikTok beauty filters and the influence it gives on their self-image and self-esteem. Twenty (20) female adolescents from Poblacio?n, Veruela, Agusan del Sur were chosen through convenient sampling. A face-to-face in-depth interview with open-ended questions was conducted to explore more views regarding the influence of TikTok beauty filters on their self-image and self-esteem. Results showed that female adolescents regularly consume TikTok beauty filters, which means they are highly exposed to problematic beauty messages. Their constant exposure to TikTok beauty filters has influenced their beauty perceptions. They also revealed that bullying, societal pressure, insecurities, social media influence, bandwagon, and peer influence are the lived experiences that led them to use TikTok beauty filters. Their perceptions of beauty from TikTok beauty filter exposure have led to self-discrepancies which further influenced their self-image and self-esteem